The role of endoscopic ultrasound guidance for biliary and pancreatic duct access and drainage to overcome the limitations of ERCP: a retrospective evaluation - García-Alonso, Francisco Javier; Peñas-Herrero, Irene; Sanchez-Ocana, Ramon; Villarroel, Mariano; Cimavilla, Marta; Bazaga, Sergio; De Benito Sanz, Marina; Gil-Simon, Paula; de la Serna-Higuera, Carlos; Perez-Miranda, Manuel (Endoscopy, 2020)
Background Endoscopic ultrasound (EUS)-guided ductal access and drainage (EUS-DAD) of biliary/pancreatic ducts after failed endoscopic retrograde cholangiopancreatography (ERCP) is less invasive than percutaneous transhepatic biliary drainage (PTBD). The actual need for EUS-DAD remains unknown. We aimed to determine how often EUS-DAD is needed to overcome ERCP failure.Methods Consecutive duct access procedures (n = 2205; 95 % biliary) performed between June 2013 and November 2015 at a tertiary-care center were reviewed. ERCP was used first line, EUS-DAD as salvage after ERCP, and PTBD when both had failed. Procedures were defined as “index” in patients without prior endoscopic duct access and “combined” when EUS-DAD followed successful ERCP. The main outcomes were the EUS-DAD and PTBD rates.Results EUS-DAD was performed in 7.7 % (170/2205) of overall procedures: 9.1 % (116/1274) index and 5.8 % (54/931) follow-up. Most index EUS-DADs were performed following (46 %) or anticipating (39 %) ERCP failure, whereas 15 % followed successful ERCP (combined procedures). Among index procedures, the EUS-DAD rate was higher in surgically altered anatomy (58.2 % [39 /67)] vs. 6.4 % [77/1207]); PTBD was required in 0.2 % (3/1274). Among follow-up procedures, ERCP represented 85.7 %, cholangiopancreatography through mature transmural fistulas 8.5 %, and EUS-DAD 5.8 %; no patient required PTBD. The secondary PTBD rate was 0.1 % (3/2205). Six primary PTBDs were performed (overall PTBD rate 0.4 % [9/2205]).Conclusions EUS-DAD was required in 7.7 % of ERCPs for benign and malignant biliary/pancreatic duct indications. Salvage PTBD was required in 0.1 %. This high EUS-DAD rate reflects disease complexity, a wide definition of ERCP failure, and restrictive PTBD use, not poor ERCP skills. EUS-DAD effectively overcomes the limitations of ERCP eliminating the need for primary and salvage PTBD in most cases.